International register “Dynamics analysis of comorbidities in SARS-CoV-2 survivors” (AKTIV) and the register “Analysis of hospitalizations of comorbid patients infected during the second wave of SARS-CoV-2 outbreak” (AKTIV 2) - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; Y. N. Belenkov; A. O. Konradi; Y. M. Lopatin; A. P. Rebrov; S. N. Tereshchenko; A. I. Chesnikova; H. G. Hayrapetyan; A. P. Babin; I. G. Bakulin; et al. (Российский кардиологический журнал, 2021)
The organizer of the registers “Dynamics analysis of comorbidities in SARSCoV-2 survivors” (AKTIV) and “Analysis of hospitalizations of comorbid patients infected during the second wave of SARS-CoV-2 outbreak” (AKTIV 2) is the Eurasian Association of Therapists (EAT). Currently, there are no clinical registries in the Eurasian region designed to collect and analyze information on long-term outcomes of COVID-19 survivors with comorbid conditions. The aim of the register is to assess the impact of a novel coronavirus infection on long-term course of chronic non-communicable diseases 3, 6, 12 months after recovery, as well as to obtain information on the effect of comorbidity on the severity of COVID-19. Analysis of hospitalized patients of a possible second wave is planned for register “AKTIV 2”. To achieve this goal, the register will include men and women over 18 years of age diagnosed with COVID-19 who are treated in a hospital or in outpatient basis. The register includes 25 centers in 5 federal districts of the Russian Federation, centers in the Republic of Armenia, the Republic of Kazakhstan, the Republic of Kyrgyzstan, the Republic of Belarus, the Republic of Moldova, and the Republic of Uzbekistan. The estimated capacity of the register is 5400 patients.